Perception of Stigmatization in Forensic Patients With Schizophrenia - Margetić, Branimir; Aukst-Margetić, Branka; Ivanec, Dragutin; Filipčić, Igor (2008)
Background: The literature about perceived stigmatization of forensic patients with schizophrenia is sparse. Aims: To examine relations between the perceived stigmatization of forensic patients with schizophrenia and the intensity of the symptoms, age, regular home visiting, kind of offence, perceived family support and duration of hospitalization. Method: Sixty-two male forensic patients with schizophrenia were included. Perceived stigmatization was measured by the modifi ed questions from the World Health Organization Disability Assessment Schedule II. Symptomatology was assessed with the Positive and Negative Syndrome Scale. Perception of family support was assessed with a visual-analogue scale. Due to different characteristics of offences and possibilities for home visiting, patients were divided into groups of those who had committed violent and non-violent offences, and those with and without the possibility of regular home visiting. Results: Symptoms have an impact on the perception of stigma. The kind of offence committed does not have a signifi cant role in the perception of discrimination. Age was negatively correlated with the perception of stigma. Conclusion: Results might have signifi cance for a better understanding of social relations between forensic patients and their environment and provide us with information about institutionalized forms of stigma. Results might have implications for the treatment and the quality of life of these patients.
ENG